Lie down with the devil - Barnes, Linda (St. Martin's Minotaur, 2008)
Faced with nothing but dead ends in her boyfriend Sam Gianelli's secret indictment for murder, Boston P.I. Carlotta Carlyle goes back to basics and takes a case for a nervous bride-to-be who wants to make sure her fiancé is being faithful. Simple enough, but when her client turns up dead, Carlotta catches the kind of break she wished she hadn't--From publisher description.